PENGARUH PENGGUNAAN LEMBAR KEPATUHAN PEMBERIAN TABLET TAMBAH DARAH TERHADAP KADAR HB PADA REMAJA PUTRI DI SMP NEGERI 1 TEMPEH KABUPATEN LUMAJANG - Dwizen, Handayani; Purwati, Anik; Alfitri, Rosyidah (NHM PRESS, 2024)
Anemia is a condition in which the body experiences a decrease in which the level of hemoglobin (Hb) in red blood cells is lower than the normal standard value set by WHO. This research is a type of quantitative research using a correlation research design, pre-experimental design with Univariate, Bivariate data analysis (Independent T Test). The majority of the intervention group had a menarche age of 12 years, while the majority in the control group were 13 years old, 37.5%. while the majority of Hb levels in the intervention group were 11.6 gr/dl. Meanwhile, in the control group, the majority had Hb levels of 11.8 gr / dl. Meanwhile, the p value in this study is 0.001. There is an effect of using the compliance sheet for administering blood supplement tablets on HB levels in adolescent girls at SMP Negeri 1 Tempeh Lumajang Regency